Simulation of battery discharge control schemes - Щербань, Анастасія Павлівна; Ларін, Віталій Юрійович (Technology audit and production reserves, 2016)
The main approaches to building control schemes and control of lithium-polymer batteries are analyzed in the article. Although considered possible element base is very diverse, but it is not always possible to accomplish the task. Instead, a study proposed two schemes of controller building of battery discharge level. The basis of their work is the method of controlling the accumulator battery (AB) level by measuring the voltage. The first scheme enables disconnection of the power supply from the system (and subsequent connection of backup AB) in achieving a given level of discharge, preventing recharging and previous AB breakdown. The second scheme allows to control multiple discharge levels (using the principle of LED column) by establishing four comparators, thus reflecting the whole discharge cycle. The methods of analytical research of existing capabilities of building ABs control systems for unmanned aerial vehicles and simulation techniques on the basis of Multisim 12.0 program are used during research. Implementation of the simulation model allows visually assess the performance of the proposed schemes and pay attention to possible ways of their improvement and further development. The results extend the design and use of unmanned aerial vehicles that are powered by portable power sources – Lithium-polymer batteries.